Use photogrammetry program to document the blue dome tower as a part of conservation requirement for the historical buildings in Kirkuk castle - Hasan H.Mohammed, Ghadah; Muhammed Yunus, Sumbul; Hasan Mohammed, Omar (International Journal of Engineering and Technology, 2019)
The heritage buildings are considered witnesses for city memory and its cultural legacy. Recently the attention increased concerning this legacy in accordance to informational revolution which the world observes in the field of computer technology and its role in all life fields. The computer role became clear to reserve Cultural heritage properties especially in the aspect of documentation and performance through three dimension type. Iraq is one of Middle East country which is rich of Cultural heritage treasure that extended to thousand years. Kirkuk is one of outstanding historical city, the most eminent rain is the ancient Kirkuk castle. It includes distinguished remains such as houses, the Blue Dome tower. These buildings subjected to collapses during the time periods for many different factors, so they are in sore need for documentation according to modern methods. The research pays attention to documental the blue dome mine rate which subjected to deterioration. To explain this we need acknowledge to trace the scientific and practical styles for documentation process concerning historical building by using photogrammetry program. The importance of the research appeared in necessity to find a conception about architectural documentation process use computer scientifically to get benefit of photogrammetry technology that employed to keep cultural heritage buildings. The research problem appeared at this respect ambiguity of using photogrammetry process ways to document ate cultural legacy as a part of keeping work generally and ascertainment of theological accuracy through the documentation and achievement of three dimensional photogrammetry of Blue Dome tower of Kirkuk castle in particular. The aim of the research showed 3 parts , first the study of historical and architectural features of Kirkuk Blue Dome tower and its classification as ancient historical building. Second study of the technology and its role in documentation of historical buildings. Third includes the practical application through fulfilling photogrammetry of Kirkuk Blue Dome tower, by using the instruments of software, hardware to accomplish the process. The last parts dedicated the analysis and discussion the consequences to define the final conclusions that presented to obtain coordinates of Kirkuk Blue Dome tower and its typicalization on three dimensions, keeping the information’s and coordinates as documented main source and to preserve original characteristics for ancient buildings then to the new generation if they subjected to collapses.